1988
DOI: 10.1128/jb.170.8.3327-3332.1988
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polysaccharides of Rhizobium meliloti exo mutants that form ineffective nodules

Abstract: Mutants of Rhizobium meliloti SU47 with defects in the production of the Calcofluor-binding exopolysaccharide succinoglycan failed to gain entry into alfalfa root nodules. In order to define better the polysaccharide phenotypes of these exo mutants, we analyzed the periplasmic oligosaccharide cyclic (1-2)-p-D-glucan and lipopolysaccharide (LPS) in representative mutants. The exoC mutant lacked the glucan and had abnormal LPS which appeared to lack a substantial portion of the 0 side chain. The exoB mutant had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 48 publications
6
115
0
1
Order By: Relevance
“…It is perhaps not surprising that exoB is not regulated by exoR and exoS because exoB mutants are also defective for the production of a second exopolysaccharide, EPS II (13,41), and show lipopolysaccharide alterations (4,18). Recently it has been shown that the exoB gene encodes UDP-galactose epimerase, which converts UDP-glucose to UDP-galactose (3a olism [1], and therefore exoB mutants are not galactose sensitive.)…”
Section: Resultsmentioning
confidence: 99%
“…It is perhaps not surprising that exoB is not regulated by exoR and exoS because exoB mutants are also defective for the production of a second exopolysaccharide, EPS II (13,41), and show lipopolysaccharide alterations (4,18). Recently it has been shown that the exoB gene encodes UDP-galactose epimerase, which converts UDP-glucose to UDP-galactose (3a olism [1], and therefore exoB mutants are not galactose sensitive.)…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, mutants had the same nodulation kinetic and fixed nitrogen at the same (Leigh & Lee, 1988;Canter Cremers e t al., 1990). The mutant is not mucoid and the residual EPS, isolated using the method described by Dielbold & Noel (1989), lacks galactose residues and the acidic component (Fig.…”
Section: Symbiotic Properties Of the Exob Mutantmentioning
confidence: 99%
“…It has been reported that the exoB gene is necessary for successful nodulation on legumes that develop an indeterminate type of nodule (Leigh e t al., 1985;Leigh & Lee, 1988;Canter Cremers etal., 1990), but does not seem to be essential for nodulation on legumes with a determinate type of nodule (Parniske e t al., 1993). However, we report in this paper an exoB mutant of Rhixobitlm sp.…”
Section: Symbiotic Properties Of the Exob Mutantmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, one has to be aware of the fact that particular mutations may have pleiotropic effects on the bacterial envelope components, because EPSs and lipopolysaccharides are partially composed of the same sugar subunits; therefore, the same precursors are utilized in the synthesis of both compounds (8,30). Pleiotropic mutants have already been isolated from Xanthomonas, Rhizobium, and Pseudomonas strains (e.g., 13,19,29,30). In this paper, we describe the cloning and characterization of a new gene region involved in xanthan gum synthesis.…”
mentioning
confidence: 99%